Imitation of Non-Speech Oral Gestures by 8-Month-Old Infants. (March 2017) - Diepstra, Heidi; Trehub, Sandra E; Eriks-Brophy, Alice; van Lieshout, Pascal HHM
This study investigates the oral gestures of 8-month-old infants in response to audiovisual presentation of lip and tongue smacks. Infants exhibited more lip gestures than tongue gestures following adult lip smacks and more tongue gestures than lip gestures following adult tongue smacks. The findings, which are consistent with predictions from Articulatory Phonology, imply that 8-month-old infants are capable of producing goal-directed oral gestures by matching the articulatory organ of an adult model.